Anticipatory Attitude of Millennials in High School 31 Jakarta towards Hoaxes - Amandya, Rafa Dahayu; Novitasari, Rizqi Tri; Wahyunengsih (Talenta Publisher, 2023)
Along with the rapid development of technology, the more advanced process of disseminating information. Hoax is one of the problems related to the dissemination of information. Hoax is fake news created by irresponsible people, made in such a way as to trick the readers into believing the word. The circulation of hoaxes is a concern for anyone, because of the disturbing nature of hoaxes, causing panic and other negative things. An anticipatory attitude towards hoaxes is very necessary. This study focuses on anticipatory attitudes towards hoaxes in the millennial generation at State High School 31 Jakarta. Where the millennial generation is a generation that is sensitive and active toward technological developments. So, hoax makers make them targets to read and disseminate hoax news. This study aims to determine whether the current millennial generation has implemented an anticipatory attitude toward hoaxes properly. The data collection technique was carried out with a questionnaire containing questions about anticipatory attitudes toward hoaxes that needed to be done. This research produces data that shows that the current millennial generation is quite aware of the anticipatory attitude toward hoaxes that must be done.